Peran Metadata Management dalam Meningkatkan Kualitas Data Efesiensi Pengambilan Keputusan - Aprilia Eka Putri; Muhammad Irwan Padli Nasution (Jurnal Manajemen Bisnis Digital Terkini, 2025)
In the era of digital transformation, organizations face the huge challenge of managing data that is constantly increasing in volume, variety, and speed. Metadata, as "data about data," plays an important role in providing context and structure to data, thus supporting the quality and effectiveness of its use. This article examines the role of metadata management in improving data quality and decision-making efficiency. Using a descriptive qualitative approach through literature analysis and case studies, the results of the study show that metadata management contributes to improving the accuracy, consistency, completeness, and timeliness of data. Good metadata implementation also speeds up data retrieval, minimizes misinterpretation, and supports the automation of the analytics process. In addition to the technical benefits, this article also discusses strategic aspects, such as the integration of metadata in data governance and the challenges of technology adoption. In the context of modern organizations, metadata management is not just a technical necessity, but part of an ongoing data governance strategy. Therefore, this article provides conceptual and practical insights for professionals and policymakers in building reliable and data-based information systems.